Experience capitalization for results-based planning, reporting and monitoring - Tesfaye, Seblewengel (Technical Centre for Agricultural and Rural Cooperation, 2019)
The BENEFIT Partnership in Ethiopia is using an experience capitalization approach to improve the way its plans and reports the collaboration efforts that it is promoting. A few critical reflection tools regularly seen as part of the capitalization approach have also been tried to ensure that the monitoring and evaluation processes are more meaningful and results-oriented